Characteristics of manager's and SMEs performance: the role of access to finance as a moderator - Khamis Alharbi, Raed; Bin Yahya, Sofri; Ries Ahmed, Essia (International Journal of Engineering and Technology, 2019)
Previous studies that examined the effect of characteristics of managers on the performance mainly concentrated large companies. The review of the small and medium enterprises (SMEs) literature reveals limited research has attempted to investigate the moderating effect of access to finance in SMEs, particularly in the developing countries. This study general reviews the moderating effect of access to finance on the relationship between characteristics of manager's related to age, education, experience and training and financial performance of SMEs in the developing countries. Findings of the study indicate the performance of SME vary with the choice of the characteristics of managers. Additionally, this study found that there is theoretical evidence showing the moderating effect of access to finance on relationships between characteristics and financial performance.Â
Keywords: SMEs Performance; Access to Finance; Characteristics of Manager.